Real Exchange Rate Misalignment in the Euro Area: Is the Current Development Helpful? - Jan Hajek (Charles University in Prague, Institute of Economic Studies (IES), 2016)
We use the behavioral equilibirum exchange rate (BEER) approach to examine the extent of real exchange rate misalignment in the euro area over the period 1980-2014. In a panel data setting, we find significant links between real exchange rates, relative productivity, trade balance and terms of trade. Unlike other papers related to the topic, we go further in the direction of linking the estimated misalignment to inflationary differentials. Our results indicate that a positive 1 percentage point inflationary differential between individual country and the euro area itself translates into 1.7 percentage point increase in overvaluation of the individual country's real exchange rate. We also show the extent of overvaluation in peripheral countries of the euro area has been increasing since mid-2000s. At the end of observed period this trend partially stopped due to emergence of falling prices in these economies. We discuss implications of such reversal and conclude deflation in peripheral countries of the euro area might be helpful when restoring its competitiveness.
Keywords: C21; E31; F31; F45; 330; real exchange rates; misalignment; euro area; panel data; inflationary differentials